Several dementia subtypes and mild cognitive impairment share brain reduction of neurotransmitter precursor amino acids, impaired energy metabolism, and lipid hyperoxidation - Aquilani, Roberto; Cotta Ramusino, Matteo; Maestri, Roberto; Iadarola, Paolo; Boselli, Mirella; Perini, Giulia; Boschi, Federica; Dossena, Maurizia; Bellini, Anna; Buonocore, Daniela; Doria, Enrico; Costa, Alfredo; et al. (Frontiers in aging neuroscience, 2023)
Objective: Dementias and mild cognitive impairment (MCI) are associated with variously combined changes in the neurotransmitter system and signaling, from neurotransmitter synthesis to synaptic binding. The study tested the hypothesis that different dementia subtypes and MCI may share similar reductions of brain availability in amino acid precursors (AAPs) of neurotransmitter synthesis and concomitant similar impairment in energy production and increase of oxidative stress, i.e., two important metabolic alterations that impact neurotransmission. Materials and Methods: Sixty-five demented patients (Alzheimer’s disease, AD, n=44; frontotemporal disease, FTD, n=13; vascular disease, VaD, n=8), 10 subjects with MCI and 15 control subjects (CTRL) were recruited for this study. Cerebrospinal fluid (CSF) and plasma levels of AAPs, energy substrates (lactate, pyruvate), and an oxidative stress marker (malondialdehyde, MDA) were measured in all participants. Results: Demented patients and subjects with MCI were similar for age, anthropometric parameters, biohumoral variables, insulin resistance (HOMA index model), and CSF neuropathology markers. Compared to age-matched CTRL, both demented patients and MCI subjects showed low CSF AAP tyrosine (precursor of dopamine and catecholamines), tryptophan (precursor of serotonin), methionine (precursor of acetylcholine) limited to AD and FTD, and phenylalanine (an essential amino acid largely used for protein synthesis) (p=0.03 to < 0.0001). No significant differences were found among dementia subtypes or between each dementia subtype and MCI subjects. In addition, demented patients and MCI subjects, compared to CTRL, had similar increases in CSF and plasma levels of pyruvate (CSF: p=0.023 to < 0.0001; plasma: p<0.002 to < 0.0001) and MDA (CSF: p<0.035 to 0.002; plasma: p<0.0001). Only in AD patients was the CSF level of lactate higher than in CTRL (p=0.003). Lactate/pyruvate ratios were lower in all experimental groups than in CTRL. Conclusion: AD, FTD, and VaD dementia patients and MCI subjects may share similar deficits in AAPs, partly in energy substrates, and similar increases in oxidative stress. These metabolic alterations may be due to AAP overconsumption following high brain protein turnover (leading to phenylalanine reductions), altered mitochondrial structure and function, and an excess of free radical production. All these metabolic alterations may have a negative impact on synaptic plasticity and activity.